Prototype of Monitoring System for Power Absorption and Solar Panel Maintenance on Website-Based Solar Power Plant - Ananda, Melly Wasilah; Yolanda, Desta; Anandika, Arrya (Universitas Andalas, 2024)
Solar power plants (PLTS) are a source of electrical energy that will never run out and will not damage the environment. PLTS is an alternative energy source when an electricity supply has not reached an area or has no commonly used power generation source, such as gas or water. In PLTS, solar panels are devices that need to be considered to maintain the performance of solar panels on PLTS. Several things must be considered, as solar panels must be protected from dust and dirt that can block sunlight. Solar panels should also not dry themselves after being wet with water because there will be traces of water left behind. Moisture on the surface of solar cells significantly reduces cell performance due to the disruption of the absorption and refraction of sunlight. To overcome this problem, the author proposes to design a system that can monitor the absorption of power carried out by solar panels and perform maintenance on solar panels in the form of cleaning from dust and dirt automatically and helping to dry after the rain subsides on the surface of solar panels. This system is integrated with the website so that officers can monitor through the monitoring website interface. This designed system can optimize power absorption on solar panels and help officers know the results of power absorption by solar panels.